Alcohol and Cannabis Use Disorder Symptom Severity, Conduct Disorder, and Callous-Unemotional Traits and Impairment in Expression Recognition - Blair, Robert James R.; Bashford-Largo, Johannah; Zhang, Ru; Mathur, Avantika; Schwartz, Amanda; Elowsky, Jaimie; Tyler, Patrick; Hammond, Christopher J.; Filbey, Francesca M.; Dobbertin, Matthew; Bajaj, Sahil; Blair, Karina S. (Frontiers in Psychiatry, 2021)
Background: Alcohol and cannabis are commonly used by adolescents in the United States. Both alcohol use disorder (AUD) and cannabis use disorder (CUD) have been associated with reduced emotion expression recognition ability. However, this work has primarily occurred in adults and has not considered neuro-cognitive risk factors associated with conduct problems that commonly co-occur with, and precede, substance use. Yet, conduct problems are also associated with reduced emotion expression recognition ability. The current study investigated the extent of any association between AUD and CUD symptom severity and expression recognition ability over and above any association of expression recognition ability with conduct problems (Conduct Disorder [CD] diagnostic status). Methods: In this study, 152 youths aged 12.5-18 years (56 female; 60 diagnosed with CD) completed a rapid presentation morphed intensity facial expression task to investigate the association between relative severity of AUD/CUD and expression recognition ability. Results: Cannabis Use Disorder Identification Test (CUDIT) scores were negatively associated with relatively weaker recognition accuracy for higher intensity (particularly sad and fearful) expressions while CD diagnostic status was independently associated with poorer recognition of sad expressions. AUDIT scores were not significantly associated with expression recognition ability. Conclusions: These data indicate that relative severity of CUD and CD diagnostic status are statistically independently associated with reduced expression recognition ability. As such, increased cannabis use during adolescence may exacerbate a neuro-cognitive risk factor for the emergence of aggression and antisocial behavior.